(3TQM GdYhGed GdLOjOgs - (3CMeO YUeIs ((3YeQ Hf SdjeGfs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdYGdejf GdYGedjf bGFOjf (B... (3deG cGf cJGH GdYhGed GdeYQha HGdYhGed GdLOjOI aj d eMeO Hf HjQ Ydj GdTgjQ HGdaGVd GdHQchj cJGHG aGNQG hHMQG RGNQG hPNQG (B...s
(3BNQgG (B:s
... (3EP GdMbjbI ajg dG eMGd dCf GdeQGO HGdehUhd gh Gddg JYGdi GdcHjQ GdeJYGd hCfJ NHjQ HCf aj NJe GdcJGH HgPG GdcdGf GdeSJWGH JaGDdG cGedG HdG GQJjGH hdPG de jPcQ GdTQ (B...(3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3LGeY GdTQhM hGdMhGTj ddMHTj (B2\1249s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GddZIs